Direct chiral separations of the enantiomers of phenylpyrazole pesticides and the metabolites by HPLC. Issue 1 (21st December 2016) - Gao, Jing; Qu, Han; Zhang, Chuntao; Li, Weijia; Wang, Peng; Zhou, Zhiqiang
Abstract: The enantiomeric separation of the enantiomers of three phenylpyrazole pesticides (fipronil, flufiprole, ethiprole) and two fipronil metabolites (amide‐fipronil and acid‐fipronil) were investigated by high‐performance liquid chromatography (HPLC) with a CHIRALPAK ® IB chiral column. The mobile phase was n‐ hexane or petroleum ether with 2‐propanol or ethanol as modifier at a flow rate of 1.0 mL/min. The influences of mobile phase composition and column temperature between 15 and 35°C on the separations were studied. All the analytes except ethiprole obtained complete enantiomeric separation after chromatographic condition optimization. Fipronil, flufiprole, amide‐fipronil, and acid‐fipronil obtained complete separation with the best resolution factors of 2.40, 3.40, 1.67, and 16.82, respectively, but ethiprole showed no enantioselectivity under the optimized conditions. In general, n‐ hexane with 2‐propanol gave better separations in most cases. The results showed decreasing temperature and content of modifier in the mobile phase resulted in better separation and longer analysis time as well. The thermodynamic parameters calculated according to linear the Van't Hoff equation indicated the chiral separations in the study were enthalpy‐driven. Fipronil and its two chiral hydrolyzed metabolites obtained baseline separation simultaneously under optimized conditions. Abstract :